Preparation of the future of music and pedagogical employees in Ukraine and China before presentation of the updated content of secondary school education on the principles of integration - Bezemchuk, Larysa; Yue, Wu (Professional Art Education, 2023)
The article theoretically substantiates and practically confirms the peculiarities of the training of future music and pedagogical workers in the modern conditions of standardization of the content of school art education in Ukraine and the People's Republic of China.Methods & methodology Peculiarities of implementing the updated content of art education in practical work with students based on the principles of integration were studied. The concept of "content of education", "updating the content of education", "updating the content of secondary school art education" in the context of integrated education is analyzed.The scientific novelt. Pedagogical conditions for the training of music majors of Ukraine and the People's Republic of China by means of integrated education have been clarified. The concept of the structure of the content of the educational subject "Art" has been expanded in accordance with the new requirements of the standardization of the art industry. The practical aspect of implementing the updated content of art education in lessons with schoolchildren is given.Results. Pedagogical conditions for the training of future music-pedagogical workers to solve modern problems of teaching the updated content of school art education are theoretically and practically substantiated. Among the main ones, attention is focused on creating a positive atmosphere in the process of practical work with schoolchildren; achievement of the dialogic component during the interaction between the teacher and the student in art lessons; giving priority to practical activities based on the principles of integrated education in the process of implementing the updated content of school art education. The research directions of the music-pedagogical opinion of Ukrainian and Chinese scientists regarding the principle of integrated education in the field of art education of the People's Republic of China and Ukraine were analyzed. The components of the training of future music-pedagogical workers are disclosed: motivational and cognitive; constructive-figurative; evaluative and practical, which effectively affect practical work with students in the conditions of integrated content of art school education. Practical examples of working with students in the conditions of the updated content of art school education based on the principles of integration are given.
Keywords: music teacher; updating the content of art education; higher music education of the People's Republic of China; training a future music teacher in Ukraine; integrated education